Hypertonic saline versus other intracranial-pressure-lowering agents for patients with acute traumatic brain injury: a systematic review and meta-analysis - Bernhardt, K; McClune, W; Rowland, MJ; Shah, A (Springer, 2023)
Acute traumatic brain injury (TBI) is a major cause of mortality and disability worldwide. Intracranial pressure (ICP)-lowering is a critical management priority in patients with moderate to severe acute TBI. We aimed to evaluate the clinical efficacy and safety of hypertonic saline (HTS) versus other ICP-lowering agents in patients with TBI. We conducted a systematic search from 2000 onward for randomized controlled trials (RCTs) comparing HTS vs. other ICP-lowering agents in patients with TBI of all ages. The primary outcome was the Glasgow Outcome Scale (GOS) score at 6 months (PROSPERO CRD42022324370). Ten RCTs (760 patients) were included. Six RCTs were included in the quantitative analysis. There was no evidence of an effect of HTS on the GOS score (favorable vs. unfavorable) compared with other agents (risk ratio [RR] 0.82, 95% confidence interval [CI] 0.48–1.40; n = 406; 2 RCTs). There was no evidence of an effect of HTS on all-cause mortality (RR 0.96, 95% CI 0.60–1.55; n = 486; 5 RCTs) or total length of stay (RR 2.36, 95% CI − 0.53 to 5.25; n = 89; 3 RCTs). HTS was associated with adverse hypernatremia compared with other agents (RR 2.13, 95% CI 1.09–4.17; n = 386; 2 RCTs). The point estimate favored a reduction in uncontrolled ICP with HTS, but this was not statistically significant (RR 0.52, 95% CI 0.26–1.04; n = 423; 3 RCTs). Most included RCTs were at unclear or high risk of bias because of lack of blinding, incomplete outcome data, and selective reporting. We found no evidence of an effect of HTS on clinically important outcomes and that HTS is associated with adverse hypernatremia. The included evidence was of low to very low certainty, but ongoing RCTs may help to the reduce this uncertainty. In addition, heterogeneity in GOS score reporting reflects the need for a standardized TBI core outcome set.